2022
DOI: 10.1108/emjb-03-2022-0051
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of obesity in marketing research

Abstract: PurposeIn spite of wide civic and academic interest in obesity, there are no bibliometric records of this issue in the marketing corpus. Thus, this inquiry is conceived to address this shortcoming with a bibliometric analysis of Scopus indexed articles published on the subject.Design/methodology/approachThe analysis followed a five-step science mapping approach of study design, data collection, data analysis, data visualisation and data interpretation. R programming software was used to review 88 peer reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…The prolific authors’ information helps identify leading authors and their countries in the research field (Onjewu et al , 2022). Table 2 ranks the most productive authors in OPE research by their publications, total citations received in the domain and affiliations.…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prolific authors’ information helps identify leading authors and their countries in the research field (Onjewu et al , 2022). Table 2 ranks the most productive authors in OPE research by their publications, total citations received in the domain and affiliations.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…The surge in OPE studies is possibly due to the advancement of the internet and technology.4.1.2The most prolific authors. The prolific authors' information helps identify leading authors and their countries in the research field(Onjewu et al, 2022). Table2ranks the most productive authors in OPE research by their publications, total citations received in the domain and affiliations.…”
mentioning
confidence: 99%
“…Through bibliometric analysis, the study identified four significant discourses related to the impact of COVID-19 on overall business, technologies, supply chain management, and the service industry (Verma & Gustafsson, 2020). A bibliometric analysis of obesity in marketing research conducted by Onjewu, Sadraei, and Jafari Sadeghi (2022) revealed the influence of persuasive communication and advertising on human well-being and child health. The study emphasized the need for ethical considerations in marketing strategies targeting vulnerable populations.…”
Section: Literature Reviewmentioning
confidence: 99%